Green Marketing Terhadap Brand Image Produk Lampu LED Philips di Kota Bandung - Setyaningrum, Ayu; Madiawati, Putu Nina (Agregat: Jurnal Ekonomi dan Bisnis, 2017)
This research aims to determine the influence of green marketing which consists of ecolabel, ecobrand, environmental advertising, environmental awareness, green product, green price, green promotion and demographic for brand image of Philips LED lighting products at Bandung city. In this research use descriptive quantitative method and causality. The sample in this research is part of the user of Philips LED lighting products at Bandung city that is not known with certainty amount. Data analysis and processing techniques used are validity test, reliability test, descriptive analysis, and multiple linear regression analysis. There are four variables that have influence for brand image among others are environmental advertising (1,787), environmental awareness (3,508), green product (1,808) and green price (2,211). The magnitude of the influence of green marketing for brand image is amounted 67,4%.